Solar photospheric spectrum microvariability: II. Observed relations to magnetic activity and radial-velocity modulation - Dravins, Dainis; Ludwig, Hans-Günter (Astronomy and astrophysics, 2024)
Context. The search for small exoplanets around solar-type stars is limited by stellar physical variability, such as a jittering in the apparent photospheric radial velocity. While chromospheric variability has been aptly studied, challenges remain for the observation, modeling. and understanding the much smaller fluctuations in photospheric spectral line strengths, shapes, and shifts. Aims. Extreme-precision radial-velocity spectrometers allow for highly precise stellar spectroscopy and time series of the Sun (seen as a star) enable the monitoring of its photospheric variability. Understanding such microvariability through hydrodynamic 3D models would require diagnostics from different categories of well-defined photospheric lines with specific formation conditions. Fluctuations in their line strengths may indeed be correlated with radial-velocity excursions and prove useful in identifying observable proxies for their monitoring. Methods. From three years of HARPS-N observations of the Sun-as-a-star at λ/Δλ ∼ 100 000, we selected 1000 low-noise spectra and measured line absorption in Fe I, Fe II, Mg I, Mn I, Hα, Hβ, Hγ, Na I, and the G-band. We examined their variations and likely atmospheric origins, also with respect to simultaneously measured chromospheric emission and apparent radial velocity. Results. Systematic line-strength variability is seen, largely shadowing the solar-cycle evolution of Ca II H & K emission, but to smaller extents (typically on a sub-percent level). Among iron lines, the greatest amplitudes have been seen for Fe II in the blue, while the trends change sign among strong lines in the green Mg I triplet and between Balmer lines. Variations in the G-band core are greater than of the full G-band, in line with theoretical predictions. No variation is detected in the semi-forbidden Mg Iλ> 457.1 nm. Hyperfine split Mn I behaves largely similar to Fe I. For lines at longer wavelengths, telluric absorption limits the achievable precision. Conclusions. Microvariability in the solar photospheric spectrum displays systematic signatures among various features. These measure values that are different than the classical Ca II H & K index, while still reflecting a strong influence from magnetic regions. Although unprecedented precision can be achieved from radial-velocity spectrometers, current resolutions are not adequate to reveal changes in detailed line shapes; in addition, their photometric calibration is not perfect. A forthcoming priority will be to model microvariability in solar magnetic regions, which could also provide desired specifications for future instrumentation toward exoEarth detections.
Online veröffentlicht: 27. Juni 2024
Gesehen am 09.12.2024